2016
DOI: 10.3390/su8060579
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Life Cycle CO2 Emissions of Low-Carbon Building in South Korea

Abstract: There have been much interest and many efforts to control global warming and reduce greenhouse gas (GHG) emissions throughout the world. Recently, the Republic of Korea has also increased its GHG reduction goal and searched for an implementation plan. In buildings, for example, there have been technology developments and deployment policies to reduce GHG emissions from a life cycle perspective, covering construction materials, building construction, use of buildings and waste disposal. In particular, Korea's G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(43 citation statements)
references
References 27 publications
3
39
0
1
Order By: Relevance
“…It has been shown that if higher weights are taken for factors related to technical characteristics, the usefulness increases with decreasing water to binder ratio and to a much lower extent on the proportion of fly ash or GGBS in the binder. The same relation has been reported [25,27,28,32,33] that high-performance concrete is more desired than ordinary concrete. If the dominating factor is the emission factor, increasing the ash or GGBS proportion in the binder as well as lowering the water:binder ratio increases utility.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…It has been shown that if higher weights are taken for factors related to technical characteristics, the usefulness increases with decreasing water to binder ratio and to a much lower extent on the proportion of fly ash or GGBS in the binder. The same relation has been reported [25,27,28,32,33] that high-performance concrete is more desired than ordinary concrete. If the dominating factor is the emission factor, increasing the ash or GGBS proportion in the binder as well as lowering the water:binder ratio increases utility.…”
Section: Discussionsupporting
confidence: 70%
“…Additionally, replacing cement with slug can also reduce emissions although not as much as concrete type. Cho et al [28] performed Life Cycle Assessment of a residential building in South Korea with a similar conclusion as Baek. It should be noted that replacing ordinary concrete with a high-strength one usually results in cost increase-for example, due to higher usage of expensive plasticizers.…”
Section: Introductionmentioning
confidence: 83%
“…Moreover, green technology can decrease global warming effect, acid rain, and air pollution from filth of fossil fuels (CO2, NOx, and CO). 6,7 Therefore, many research have been focused to find alternative substitute of conventional fossil fuel towards renewable and green energy 8 . The potential alternatives of energy sources are solar, wind, geothermal, biomass, and hydro due to their limitless and clean energy supply, which can be used for electricity generation, heating/cooling systems, or directly utilized in the form of bio products.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, they analysed the emissions of CO 2 by phases during the entire life cycle of a building. Cho and Chae [17] indicated that the operation phase is the most energy consuming stage of the whole life cycle of a building, and the construction period is followed by the operation phase. Tae et al [18] examine the influence of high-strength concrete as a means of low environmental impacts materials in high-rise buildings.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They maintained that the proper selection of low CO 2 emitting materials lowers the emissions by approximately 28%. According to Cho and Chae [17], lowering the impact of buildings on the environment requires the utilisation of low-carbon emitting materials. They show that buildings with low-carbon materials emit approximately 25% less carbon dioxide emissions when compared with those of the conventional buildings.…”
Section: Literature Reviewmentioning
confidence: 99%